Efficient resource allocation scheme for D2D enabled vehicular networks in secured 5G communication. (19th May 2022) - Rathee, Amit; Chaba, Yogesh
Abstract: D2D communications are regarded as one of the important technology in the 5th generation network. Due to the lack of spectrum resources, resource allocation has some uphill challenges. In this paper, we execute spectrum distribution and power allocation to attain the maximum efficiency for the resource allocation scheme in wireless channels. We try to maximize the ergodic capacity for both V2V and V2I connections while keeping reliability for every V2I link. Hybrid algorithms approach that turnout ideal resource allocation for D2D are proposed. The presentation of channels is established by MATLAB Simulation.